Tingkat Pendapatan Pedagang Kaki Lima Di Kawasan Kota Baru Kecamatan Kuta Alam - Mila Puspita; Amrusi Amrusi; Irma Anggraini (Universitas Syiah Kuala, 2021)
This study aims to determine the income of street vendors in terms of length of business, capital, trading locations and working hours in the Kota Baru area, Kuta Alam District and the constraints of street vendors in increasing income in the Kota Baru area, Kuta Alam District. This research approach is a qualitative approach and the type of descriptive research. The research respondents were 15 traders in the Kota Baru area, Kuta Alam District. Data was collected by using interview techniques, observation and literature study. The results showed that the income of street vendors in the Kota Baru area, Kuta Alam district, from permanent work as traders was an average of Rp. 403.333/ day. The lowest income was obtained by the grocery kiosk, which was Rp. 250,000/day, while the highest income was obtained by the Beverage seller of Rp. 550,000/day. The constraints of street vendors in increasing income in the Kota Baru area, Kuta Alam District, are the increasing number of traders selling the same merchandise, rising prices of goods in the market so that street vendors need a lot of capital and the security of selling locations from various Banda Aceh City government policies.Keywords: Street Vendors, Income, Kota Baru